Vehicle Monitoring System Using Motion Detection Algorithms For USM Campus. - Osman, Mohd. Azam; Talib, Abdullah Zawawi; Tan, Kian Lam; Wong, Poh Lee; Sabudin, Maziani (2007)
Maintaining security in university campuses is most definitely the talk of today. problems surface when security personnel need to constantly patrol the campus grounds to ,monitor activities of vehicles. With the possible introduction of the motion detection and character recognition algorithms in security systems of the future, vehicle identities such as license plate numbers can be captured and processed at the security post to make it possible for the vehicles to be monitored remotely.